Dental health status in elderly (Gorgan –Iran) - Modanloo MM (MSc); Khosravee H (MD); Ghobadee Kh (BSc); Abdollahi H (BSc); Ziaea T (MSc); Behnampour N (MSc) (مجله دانشگاه علوم پزشکی گرگان, 2010)
Background and Objective: Ageing is a bio-cognitive which can be described as a progressive and degenerating process in human. One of the major changes in the elderly is loss of teeth, which can affect on dietary intake and nutritional status. This study was designed to assess the dental health in elderly people in Gorgan, North of Iran. Materials and Methods: This descriptive and cross-sectional study was conducted on 400 subjects (211 female and 189 male) aged 60 years and above in two selected health centers in Gorgan-Iran. Data were collected by questionnaire and oral and dental examination. Data was analyzed by using SPSS-13 software and chi-square test. Results: The mean age of the subjects were 66.7+-6.7 Sixty percent of the participants were without natural teeth and forty percent had natural teeth. only 10.5 percent of subjects had complete natural teeth. 19.7 participants had decayed teeth. The mean of decayed teeth was 9.2 (rang 1-28) and filled teeth was 4.8 (rang 1-16) in 12.5 percent of participants. Age, level of education and level of income were significantly associated with the number of existed teeth (P<0.05). Conclusion: In regard to high prevalence of without natural and decay teeth in the elderly population, this study, it is recommended the serial assessment of dental health to be screened on routine bases.